A prospective study of functional outcome of closed displaced mid-shaft clavicle fractures treated with intramedullary titanium elastic nail system - Kumar, Mallepogu Kiran; Prasad, Rajana Siva (International Journal of Research in Orthopaedics, 2020)
Background: Clavicle fractures are most common injuries in young and active individuals, especially those who participate in sports where high-speed falls (e.g., bicycling, motorcycles) or violent collisions (e.g., Football, hockey) are frequent. In contrast, in children and elderly, they are related to falls, and they account for approximately 2.6% of all fractures. The most common site of fracture is a middle-third shaft; it accounts for 80% of all clavicle fractures. Methods: This was a prospective study carried in 20 patients with simple mid third clavicular fractures, who were treated with closed intra-medullary fixation with TENS nailing. Post-operatively range of movements, ability to get back to routine work were assessed and noted. Results: At the end of the study, all the 20 patients in the follow-up group with 14 male and 6 female patients. The mean age was 34.9 years (between 22-55 years) in the group. The mean time interval between injury and surgery was 3.55 days (range 1-6 days). All the patients are achieved clinical and radiological union at a mean of 8.6 weeks (range, 6-12 weeks). Conclusions: Thus, the intramedullary fixation of a displaced midshaft clavicle fracture is a safe minimally invasive technique. The present study advises the use of minimally invasive antegrade titanium elastic nail for fixation of displaced midshaft clavicle fractures. Although, for comminuted fractures plating remains the procedure of choice.